Antena Ultrawideband Multiple Input Multiple Output (MIMO) Dengan Struktur Dekopling Pada Ground - tiara, Rini; Firdaus, Firdaus; Maria, Popy; Yulindon, Yulindon (Elektron : Jurnal Ilmiah, 2023)
The advancement of technology demands an acceleration in data transmission, where the utilization of UWB MIMO presents a solution to address this issue. However, the implementation of MIMO techniques involving multiple transmitters and receivers leads to an increase in mutual coupling values. This results in a decline in antenna performance. Therefore, a decoupling structure on the ground is employed to minimize mutual coupling values and enhance isolation. The progress of technology calls for expedited data transmission, where the utilization of UWB MIMO presents a solution to address this issue. However, the use of MIMO techniques with numerous transmitters and receivers escalates mutual coupling values. This subsequently leads to a degradation in antenna performance. Hence, a decoupling structure on the ground is employed to minimize mutual coupling values as much as possible and enhance isolation. In this research, a UWB MIMO antenna was designed utilizing a 30 × 40 mm FR-4 Epoxy substrate with a thickness of 0,8 mm and a dielectric constant of 4,4. The antenna was designed using CST Studio 2019 software, followed by fabrication, and subsequently, a comparison was drawn between the simulation and fabrication results.The obtained results have fulfilled the UWB antenna specifications within the frequency range of 3,07 GHz to 11 GHz, with simulated mutual coupling values lower than -15 dB and an envelope correlation coefficient (ECC) value less than 0,01. The resulting radiation pattern is omnidirectional. During the measurements, mutual coupling values of less than -15 dB and good isolation is found within the frequency range of 4,3 GHz to 11 GHz